2007
DOI: 10.1111/j.1863-2378.2007.01074.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Introduction of Avian Influenza Virus into Commercial Layer Chicken Farms During the Outbreaks Caused by a Low‐Pathogenic H5N2 Virus in Japan in 2005

Abstract: Avian influenza outbreaks caused by a low-pathogenic H5N2 virus occurred in Japan from June to December 2005. All 41 affected farms housed layer chickens. Therefore, we conducted a case-control study targeting all commercial layer chicken farms within the movement restriction areas in Ibaraki prefecture, where most outbreaks were detected, to investigate the risk factors for the introduction of avian influenza virus (AIV). Four variables were identified as risk factors associated with the introduction of AIV b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 12 publications
4
41
1
Order By: Relevance
“…Increasing density of poultry is associated with a higher contact rate between susceptible and infected birds and therefore greater risk of spread [29][30][31][32][33][34]. However, no association was found between poultry density and the risk of HPAIV infection in China, suggesting that this unexpected finding was due to a greater proportion of industrialized chicken production at higher poultry densities, with associated higher biosecurity standards and vaccination protocols.…”
Section: Poultry Densitycontrasting
confidence: 47%
“…Increasing density of poultry is associated with a higher contact rate between susceptible and infected birds and therefore greater risk of spread [29][30][31][32][33][34]. However, no association was found between poultry density and the risk of HPAIV infection in China, suggesting that this unexpected finding was due to a greater proportion of industrialized chicken production at higher poultry densities, with associated higher biosecurity standards and vaccination protocols.…”
Section: Poultry Densitycontrasting
confidence: 47%
“…Causally this factor plays an important role in the spread of infection, both as windborne spread, if the distance between farms is less than 50 meters [27] and mechanical transfer by other routes e.g. human movement between farms [13]. The large effect size and the wide CIs were a concern for this variable, not because the association may not be true, but because of the effect on the model and the estimation process where there are cells with small numbers of observations affecting precision.…”
Section: Discussionmentioning
confidence: 99%
“…Many published articles have quantified different risk factors for various subtypes of avian influenza in commercial poultry farms all over the world [1023]. Previously published studies have demonstrated that avian influenza introduction, transmission and persistence are associated with poultry trading pattern [12, 20], human and poultry densities [18, 23], movement of human and fomites [10, 12, 14], low biosecurity [10, 13, 21, 22], proximity to water bodies [15, 16, 17, 23], distance from other commercial poultry farms [11, 13, 21], and proximity to roads [15, 16, 19]. These risk factors help to further identify high-risk farms/systems, which could be targeted for interventions such as vaccination or culling.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, tracing of epidemiological movements between farms conducted by the prefecture revealed that there were several companies whose farms were located inside the cluster, and risk materials and pepole, such as live chickens, vehicles and farm crews, had been moving between related farms before movement restriction was in place. Introduction of infected birds and contaminated fomites (egg trays, bird cages and farm equipment) or personnel are important risk factors for spreading the virus [1,12,17]. Therefore, it is thought that the virus was disseminated to contact farms through the movement of risk materials.…”
mentioning
confidence: 99%